Predicting teachers’ use of digital technology - Siti Syuhada Abu Hanifah; Norliza Ghazali; Ahmad Fauzi Mohd Ayub; Rosfuzah Roslan (Institute of Advanced Engineering and Science, 2023)
In recent years, the use of digital technology and its relationship to the ability known as digital competence has become a core concept in discussions about the skills that individuals should possess in a knowledge society. Teachers’ skills in using digital technology are becoming a critical component of developing practical pedagogical knowledge for practice and student learning enhancement. The purpose of this study is to predict the factors that influence secondary school teachers when it comes to using digital technology. This study will establish relationships between personal innovativeness, technology self-efficacy, attitude toward digital technology, and digital competence. In Pahang, Malaysia, a survey was conducted with 493 secondary school teachers from 50 public secondary schools of 11 districts. Proportionate stratified sampling, cluster random sampling, and simple random sampling were used to obtain samples. The findings have established that technology self-efficacy, attitude towards digital technology, and digital competence significantly affect how teachers use digital technology. These findings emphasize the importance of increasing teachers’ digital competence as well as numerous elements that influence teachers’ use of digital technology to fulfill the expectations of future qualified professions and thus prepare students for their future.